The Degree To Which English Teachers Practice The Skills Of Scientific Thinking In Their Classrooms (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The purpose of the research The degree of practicing English teachers in Damascus is based on the skills of scientific thinking in their classrooms, as well as the differences in the degree of practicing these skills according to gender variables and the number of years of teaching experience. The sample consisted of (62) teachers, They were chosen by the sample of the sample from the schools in Damascus city and applied the measure of scientific thinking skills prepared by the researcher after verifying his sincerity and stability. The results indicated that: 1. The existence of a generally low degree in English teachers in the degree of exercise of the skills of scientific thinking in their classrooms, and the degree of practice of English teachers of the skills of scientific thinking subsidiary was as follows: - A high degree of teachers in the exercise of the skill of scientific thinking related to (gathering information). - A medium degree for teachers in the exercise of scientific thinking skills related to (concentration - memory - organization - analysis). - Low degree of teachers in the exercise of scientific thinking skills related to (obstetrics). - Very low degree of teachers in the exercise of scientific thinking skills related to (evaluation - integration). 2 - There are no statistically significant differences in the average grade of English teachers in the degree of practicing the skills of scientific thinking in their classes according to the gender variable. 3- There are statistically significant differences in the average grade of English teachers in the exercise of scientific thinking skills on the total score of the scale and its sub-fields according to the variable number of years of teaching experience for teachers with higher teaching experience except for the following fields (concentration skill / information gathering / analysis / integration / Evaluation), where differences were not statistically significant.